Dissolving microneedles developed in association with nanosystems : a scoping review on the quality parameters of these emerging systems for drug or protein transdermal delivery - Weimer, Patrícia (2021)
The largest organ of the body provides the main challenge for the transdermal delivery of lipophilic or high molecular weight drugs. To cross the main barrier of the skin, the stratum corneum, many techniques have been developed and improved. In the last 20 years, the association of microneedles with nanostructured systems has gained prominence for its versatility and for enabling targeted drug delivery. Currently, the combination of these mechanisms is pointed to as an emerging technology; however, some gaps need to be answered to transcend the development of these devices from the laboratory scale to the pharmaceutical market. It is known that the lack of regulatory guidelines for quality control is a hindrance to market conquest. In this context, this study undertakes a scoping review of original papers concerning methods applied to evaluate both the quality and drug/protein delivery of dissolving and hydrogel-forming microneedles developed in association with nanostructured systems.